Teacher Guidance and Counseling with Al-Islam and Kemuhammadiyahan in Ajatappareng Region: Learning Styles and Models of Islamic Education - Elihami Elihami; Agung Agung (Universitas Muhammadiyah Enrekang, 2021)
A novel survey instrument was developed to evaluate the motivations of teacher educators for entering the profession, as well as the relationships between teacher guidance and counseling with Al-Islam and Kemuhammadiyahan in ajatappareng region. We identified four reasons using data from 102 teacher educators educating in-service teachers: professional goals, social contribution, escape routines, and coincidence. While escape routines is a 'push' element related to emotional tiredness in teachers, career goals are a 'pull' factor related to job satisfaction in teacher educators. The measure can be used for self-evaluation in the recruitment of teacher educators.